2014
DOI: 10.1097/mao.0000000000000514
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Assisted Dissection by Means of Mesna in Cholesteatoma Surgery

Abstract: This study showed that chemically assisted dissection by using mesna represents a valid support in reducing the frequency of residual disease in cholesteatoma surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Vincenti et al . 14 conducted a retrospective study on Mesna topical application in canal wall up mastoidectomy. They included 214 patients: 108 underwent operation with the ancillary use of Mesna (chemically assisted dissection group), and 106 were treated with the traditional mechanical technique alone (no chemically assisted dissection group).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vincenti et al . 14 conducted a retrospective study on Mesna topical application in canal wall up mastoidectomy. They included 214 patients: 108 underwent operation with the ancillary use of Mesna (chemically assisted dissection group), and 106 were treated with the traditional mechanical technique alone (no chemically assisted dissection group).…”
Section: Resultsmentioning
confidence: 99%
“…17 In recent years, there has been an increase in indications for Mesna as a support tool for surgical dissection especially in the ENT field. 14 With the hypothesis that the physiological and pathological adhesions between different layers are rich in disulphide bonds, and bearing in mind that some drugs already in use have the ability to break these bonds, Zini et al . 8 developed a research project entitled ‘chemically assisted dissection’ and, among various substances, chose Mesna for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that application of MESNA dissects tissue layers during cholestea-toma or atelectatic ear surgeries by breaking the disulfide bonds of the matrix. MESNA has also been reported to increase success rates of surgery and decrease rates of residual cholesteatoma formation 33,34 . In this study, there was no residual cholesteatoma in the MESNA group, while there was one in the non-MESNA group.…”
Section: Discussionmentioning
confidence: 99%
“…Among methods facilitating removal of the matrix from the fistula laser [21], special techniques, e.g., underwater ear surgery [22] and mesna [23] are described. We do not have experience with the first mentioned method, but we appreciate significant role of mesna in atraumatic LF clearance.…”
Section: Discussionmentioning
confidence: 99%